The practice of postgraduate students' publication: A qualitative analysis on the students' publication challenges - Syarief Fajaruddin; Caly Setiawan; Tri Andi; Nuryani Dwi Astuti; Ari Setiawan; I Nyoman Indhi Wiradika; Satrian Suhendar (Universitas Sebelas Maret, 2026)
Scientific publication in reputable international journals is a key requirement for the graduation of postgraduate students in Indonesia. Although this policy aims to enhance research quality, many students face challenges in fulfilling these requirements. This study aims to explore the scientific publication practices of postgraduate students and identify the difficulties they encounter in the publication process. The research method employs a qualitative approach with a phenomenological design. Data were collected through participatory observation and in-depth interviews with postgraduate students selected using purposive sampling, and analyzed using ATLAS.ti 22 software. The findings reveal that the requirement to publish in Scopus-indexed journals with a minimum Q3 rating, as well as the obligation to include the supervisor and co-supervisor as authors, presents significant challenges for students. The difficulties faced include structuring articles properly, developing the research gap, determining the novelty of the research, and using appropriate academic language. The implications of these findings highlight the importance of more intensive support from higher education institutions in providing technical and pedagogical guidance to help students overcome these challenges and better prepare them to meet international publication standards.